The early retirement challenge for fossil fuel power plants in deep decarbonisation scenarios. (August 2018) - Kefford, Benjamin M.; Ballinger, Benjamin; Schmeda-Lopez, Diego R.; Greig, Chris; Smart, Simon
Abstract: Rapid decarbonisation of the global energy sector will likely have a multitude of economic consequences, including the premature decommissioning of most fossil fuel power plants. In this analysis, we examine the impact of early retirements for oil, coal, and natural gas-fired generators required to follow a given 2 °C emissions trajectory (the IEA 2DS) and explore the policy implications surrounding this challenge. Modelling the period up to 2060, the drop in retirement age required to meet this scenario potentially creates $541 billion worth of stranded power plant assets across the US, EU, China, and India alone. In some cases, coal plants built within the past 5 years will need to be retired after only half the nominal operating lifetime. Regional analysis exposed disproportionate impacts in China and India, shouldering the vast majority of the costs and amplifying concerns over energy access and affordability. Policies such as burden-sharing for equitable mitigation, investment into CCS technology, and international financial compensation are discussed as potential avenues for mitigating this impact. However, limitations in all avenues highlight the need for further consideration of the inferred requirement to force early retirements, in order to avoid exacerbating regional imbalances and improve the feasibility of imposed targets. Highlights: We quantify the potential for stranded fossil fuel power plants in a 2 °C scenario. $541 billion worth of stranded fossil fuel power plants could be created by 2060. Coal plants will require retirement after 20–30 years of operation in China & India. Energy poverty concerns and continued investment exacerbates the issue. Allocating the cost of early retirements among countries poses severe controversy.